Dilemmas, conspiracies, and Sophie’s choice: vignette themes and ethical judgments - Mudrack, Peter E.; Mason, E. Sharon (My University, 2014)
Knowledge about ethical judgments has not advanced appreciably after decades of research. Such research, however, has rarely addressed the possible importance of the content of such judgments; that is, the material appearing in the brief vignettes or scenarios on which survey respondents base their evaluations. Indeed, this content has seemed an afterthought in most investigations. This paper closely examined the vast array of vignettes that have appeared in relevant research in an effort to reduce this proliferation to a more concise set of overarching vignette themes. Six generic themes emerged from this process, labeled here as Dilemma, Classic, Conspiracy, Sophie’s Choice, Runaway Trolley, and Whistle Blowing. Each of these themes is characterized by a unique combination of four key factors that include the extent of protagonist personal benefit from relevant vignette activities and victim salience in vignette descriptions. Theme identification enabled inherent ambiguities in vignettes that threaten construct validity to come into sharp focus, provided clues regarding appropriate vignette construction, and may help to make sense of patterns of empirical findings that heretofore have seemed difficult to explain.
Keywords: Ethical judgments; Vignette themes; Literature Review